Teacher Creativity Development in Creative Learning - Yani Fitriyani; Nana Supriatna; Mia Zultrianti Sari (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aimed to reveal the creativity of teachers in creative learning in social studies subjects in grade 6 of elementary school. This research used descriptive qualitative research method. The research subjects consisted of the principal, teachers and grade 6 of elementary school students. Data collection was carried out by interviewing and observing and recording documents. Data analysis used interactive analysis, namely data reduction, data presentation, and drawing conclusions. The results of this study indicated that; (1) the teacher has been creative in presenting learning material for the proclamation of Indonesian independence by using imaginative concepts, stimulating original ideas and works, applying variations in interaction patterns, teaching styles, and various messages, and applying direct evaluation, (2) the teacher is creative in applying the teaching method used with the application of brainstorming method and combining existing methods, (3) the teacher has been creative in developing learning media and learning resources by producing homemade media. In conclusion, creative teachers are teachers who are able to develop pedagogical abilities, life skills, increase values and build and develop professional attitudes according to the era of globalization.